2022
DOI: 10.1371/journal.pone.0272418
|View full text |Cite
|
Sign up to set email alerts
|

“Kind of blurry”: Deciphering clues to prevent, investigate and manage prescribing cascades

Abstract: Background Prescribing cascades, where a medication is used to treat the side effect of another medication, contribute to polypharmacy and related morbidity. Little is known about clinicians’ and patients’ experiences with prescribing cascades. In this study, we explored why and how prescribing cascades occur across a variety of care settings and how they are managed. Methods and findings This descriptive qualitative study employed semi-structured interviews with older adults who may have experienced a presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Finding an association between the initial drug therapy, a new medical condition, and the prescribing of a new drug therapy can be facilitated by knowing three pieces of information: when a drug was started, why it was started, and who started it. 19 This information allows the sequence of prescribing indicating a prescribing cascade to become clear and potentially avoids additional investigations that may be initiated to rule out potentially more serious diagnoses. 28 Further, it is important to F I G U R E 2 Cumulative incidence of serious adverse events in the 90-day follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding an association between the initial drug therapy, a new medical condition, and the prescribing of a new drug therapy can be facilitated by knowing three pieces of information: when a drug was started, why it was started, and who started it. 19 This information allows the sequence of prescribing indicating a prescribing cascade to become clear and potentially avoids additional investigations that may be initiated to rule out potentially more serious diagnoses. 28 Further, it is important to F I G U R E 2 Cumulative incidence of serious adverse events in the 90-day follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…11 We know from individual case reports and qualitative interviews that prescribing cascades are associated with the development of adverse events including confusion, 17 incontinence, 12 and head injury, 18 and have important impacts on the quality of life. 19,20 Yet, we know little about the downstream impact that prescribing cascades can precipitate at a population-level, requiring emergency room visits and hospitalizations. 10 In this study, we use a population-based cohort of older women and men who did, and did not, experience a CCB-diuretic prescribing cascade 10 to compare the rate of subsequent serious adverse events (SAE), as measured by emergency room visits or hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we wanted to explore its utilization in identifying potentially problematic medications involved in prescribing cascades, which occur when drug‐induced adverse events of a new medication trigger the prescribing of an additional new medication. Prescribing cascades are considered important contributors to polypharmacy and targets for deprescribing 34‐36 . Here, we utilized a previously published review that has identified all available prescribing cascades using a distinct methodology, the sequence symmetry analysis (SSA) 37 .…”
Section: Methodsmentioning
confidence: 99%
“…To highlight some of these phenomena and to help others identify and manage them, we have published a number of case reports (see Table 1) and the results of related interviews with our patients and GDH clinicians. 1,3,4 The rise of serotonergic agents and related toxicity…”
Section: Barbara Farrellmentioning
confidence: 99%